2009
DOI: 10.1021/om900035r
|View full text |Cite
|
Sign up to set email alerts
|

73Ge NMR Spectral Investigations of Singly Bonded Oligogermanes

Abstract: The synthesis of the two digermanes Bu s 3GeGePh3 and PhMe2GeGePh3, as well as the branched tetragermane PhGe(GeBu n 3)3, was achieved using the hydrogermolysis reaction. These species were fully characterized by NMR (1H, 13C) spectroscopy and elemental analysis, and the crystal structure of PhMe2GeGePh3 was determined. These three species, along with 11 other oligogermanes, were also characterized by 73Ge NMR spectroscopy. Chemical shifts of the 73Ge NMR resonances for these oligogermanes have been correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 32 publications
(89 reference statements)
2
47
1
1
Order By: Relevance
“…We have characterized a number of oligogermanes using 73 Ge NMR spectroscopy and have found a general trend in chemical shift values relative to Me 4 Ge at d 0 ppm, where triorganosubstituted germanium atoms R 3 Ge-exhibit resonances between d À30 and À65 ppm while resonances for diorganosubstituted germanium atoms R 2 Ge-appear in the range d À100 and À120 ppm [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have characterized a number of oligogermanes using 73 Ge NMR spectroscopy and have found a general trend in chemical shift values relative to Me 4 Ge at d 0 ppm, where triorganosubstituted germanium atoms R 3 Ge-exhibit resonances between d À30 and À65 ppm while resonances for diorganosubstituted germanium atoms R 2 Ge-appear in the range d À100 and À120 ppm [15].…”
Section: Resultsmentioning
confidence: 99%
“…Several branched oligogermanes that contain a germanium atom attached to only one substituent RGe-have been characterized using this method including (Ph 3 Ge) 3 GeH (1) [4,5], (Ph 3 Ge) 3 GePh (2) [15], and (Bu n 3 Ge) 3 GePh (4) [15]. The resonances for the central germanium atoms in 2 and 4 were observed at d À202…”
Section: Resultsmentioning
confidence: 99%
“…Me 3 GeBr was obtained using published procedure [30]. 1 H NMR (400 MHz), 13 C NMR (100 MHz) and 19 F (376.4 MHz) spectra were recorded with a Bruker 400 spectrometer (in CDCl 3 at 295 K). Chemical shifts are given in ppm relative to internal Me 4 Si ( 1 H and 13 C NMR spectra) or internal CFCl 3 ( 19 F spectra).…”
Section: General Methods and Remarksmentioning
confidence: 99%
“…Ge(SO 3 ) 3 ) 13. C NMR (100 MHz, CDCl 3 , ppm): d ¼ 138.16, 135.21, 128.43, 128.19 (aromatic carbons), À0.84 (CO 3 ).…”
mentioning
confidence: 99%
“…Our synthetic methodology can be employed for the systematic variation of not only the number of germanium atoms in the GeeGe backbone but also of the organic substituents attached to the germanium atoms in the chain. This was not possible using other previously reported synthetic methods, and we have prepared both linear [41,42,44,45] and branched [43] oligogermane systems using this method. It has been demonstrated that both the number of catenated germanium atoms and the electronic attributes of the attached organic substituents affect the relative energies of the frontier orbitals in these systems.…”
Section: Introductionmentioning
confidence: 99%